High‐Q 2D Lithium Niobate Photonic Crystal Slab Nanoresonators. Issue 5 (7th April 2019) - Li, Mingxiao; Liang, Hanxiao; Luo, Rui; He, Yang; Lin, Qiang
Abstract: Lithium niobate (LN), known as the "silicon of photonics, " exhibits outstanding material characteristics with great potential for broad applications. Enhancing light–matter interaction on the nanoscale would result in intriguing device characteristics that enable new physical phenomena to be revealed and novel functionalities inaccessible by conventional means to be realized. High‐Q 2D photonic crystal (PhC) slab nanoresonators are particularly suitable for this purpose, which, however, remains an open challenge to be realized on the lithium niobate platform. Here, an important step is taken toward this direction, demonstrating 2D LN PhC slab nanoresonators with optical Q as high as 3.51 × 10 5, about three orders of magnitude higher than other 2D LN PhC structures reported to date. The high optical quality, tight mode confinement, together with specific polarization characteristics of the devices enable the peculiar anisotropy of photorefraction quenching and unique anisotropic thermo‐optic nonlinear response to be revealed. They also allow the observation of third‐harmonic generation in on‐chip LN nanophotonic devices, and a strong orientation‐dependent generation of the second harmonic. Abstract : An important step to enhance the nanoscale lightmatter interaction on the lithium niobate platform is taken by demonstrating high‐quality two‐dimensional lithium niobate photonic crystal‐slab nanoresonators. Together with the specific polarization characteristics of the devices, the peculiar anisotropy of photorefraction quenching, the thermo‐optic nonlinear response, and the strong orientation‐dependent harmonic generation of these nanoresonators are revealed.